2020
DOI: 10.1007/s12325-020-01589-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine on Kidney Function in Chronic Kidney Disease with Subclinical Hypothyroidism in US Veterans: A Retrospective Observational Cohort Study

Abstract: Introduction Chronic kidney disease (CKD) may be associated with overt or subclinical hypothyroidism [SCH; defined as elevated serum thyroid-stimulating hormone (TSH) despite normal free thyroxine levels). Although some studies have demonstrated that thyroid replacement therapy may improve renal function in overt hypothyroidism, there is no consensus on its benefits in SCH. Clinical and limited economic outcomes were evaluated in levothyroxine-treated US veterans with CKD + SCH. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Recently, a retrospective database analysis on LVT treatment in CKD and SCH patients showed an absence of the overall benefit in eGFR; however, LVT use shortens the length of hospital stay. [ 42 ] There is possibly no association between low free thyroxine levels and CKD progression. [ 43 ] The progression of CKD was higher in the presence of proteinuria, with no effect on thyroxine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a retrospective database analysis on LVT treatment in CKD and SCH patients showed an absence of the overall benefit in eGFR; however, LVT use shortens the length of hospital stay. [ 42 ] There is possibly no association between low free thyroxine levels and CKD progression. [ 43 ] The progression of CKD was higher in the presence of proteinuria, with no effect on thyroxine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the available data have been obtained in a retrospective observational cohort study of US Veterans, where levothyroxinetreated (n: 157) and nontreated CKD (n:157) + ScH patients followed for 24 months were analyzed for clinical outcomes. Despite an absence of overall benefit on eGFR or CKD progression, it was revealed that levothyroxine use was associated with a lower length of hospital stay for reasons related to CKD, which may translate into a possible economic benefit (33). Furthermore, in a previous retrospective Korean study, the decrease in renal function in 113 CKD patients with ScH was attenuated with levothyroxine after two years (34).…”
Section: Discussionmentioning
confidence: 99%